2013
DOI: 10.1051/0004-6361/201221005
|View full text |Cite
|
Sign up to set email alerts
|

Eruptions of two flux ropes observed by SDO and STEREO

Abstract: Aims. We report for the first time the hot and cool components of two flux ropes simultaneously observed by SDO and STEREO, and the relationship between the flux rope eruptions and the coronal mass ejection (CME). Methods. Employing SDO and STEREO A and B observations, we investigated the eruptive event of two flux ropes and their associated activities in active region (AR) 11402 on January 23, 2012. Results. In SDO/AIA 94 Å (∼6.4 MK) and 131 Å (∼10 MK) images, a twisted flux rope appeared from 00:44 UT, which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
36
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(41 citation statements)
references
References 24 publications
5
36
0
Order By: Relevance
“…Only in a small percentage of cases can we exclude the presence of a flux rope. Moreover, additional studies, directly involving AIA, have shown that flux ropes are formed and ejected during a CME (Chen 2011;Li & Zhang 2013). From a theoretical point of view, a number of studies have shown that the ejection of a flux rope is sufficient to reproduce the main observed features of CMEs: Török & Kliem (2007), Fan (2010), and Aulanier et al (2010) explain the ejection with the occurrence of a Torus instability; Fan (2009) and Archontis et al (2009) with a flux emergence event; Savcheva et al (2012) with the rotation of footpoints; Amari et al (2003) with shearing and flux cancellation, while Amari et al (2011) use convergence of foot points; finally Roussev et al (2012) consider a global reorganisation of the solar corona.…”
Section: Introductionmentioning
confidence: 99%
“…Only in a small percentage of cases can we exclude the presence of a flux rope. Moreover, additional studies, directly involving AIA, have shown that flux ropes are formed and ejected during a CME (Chen 2011;Li & Zhang 2013). From a theoretical point of view, a number of studies have shown that the ejection of a flux rope is sufficient to reproduce the main observed features of CMEs: Török & Kliem (2007), Fan (2010), and Aulanier et al (2010) explain the ejection with the occurrence of a Torus instability; Fan (2009) and Archontis et al (2009) with a flux emergence event; Savcheva et al (2012) with the rotation of footpoints; Amari et al (2003) with shearing and flux cancellation, while Amari et al (2011) use convergence of foot points; finally Roussev et al (2012) consider a global reorganisation of the solar corona.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Zhang et al (2012) and Cheng et al (2013a) reported the existence of EUV hot channels that appeared in the high temperature passbands of the Atmospheric Imaging Assembly (AIA) telescope (Lemen et al 2012) tens of minutes before the eruption. Once the impulsive acceleration phase starts, the hot channel erupts upward and develops into a semicircular shape (also see Liu et al 2010a;Patsourakos et al 2013;Li & Zhang 2013a). Detailed morphology and kinematic analyses suggest that the hot channel is most likely to be the MFR and plays a critical role in forming and accelerating the CME in the inner corona (Cheng et al 2013a(Cheng et al , 2013bPatsourakos & Vourlidas 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Often magnetic flux ropes in the low corona are considered the main progenitors of CMEs, where an initial period of stability of the flux rope is followed by a fast and sudden ejection outwards into interplanetary space. This scenario is supported by a number of observations (Howard & DeForest, 2014;Chintzoglou et al, 2015;Cheng et al, 2011;Li & Zhang, 2013). Some models explain the flux rope formation and the subsequent ejection with photospheric flows (Mackay & van Ballegooijen, 2006a;Xia et al, 2014), others focus on magnetic flux emergence from underneath the photosphere (Archontis & Hood, 2012), and finally others rely on the onset of MHD instabilities (Török & Kliem, 2005;Zuccarello et al, 2015).…”
Section: Introductionmentioning
confidence: 74%